2012
DOI: 10.1176/appi.neuropsych.11020052
|View full text |Cite
|
Sign up to set email alerts
|

The Neuropsychiatry of Vitamin B12 Deficiency in Elderly Patients

Abstract: Vitamin B12 deficiency is a common cause of neuropsychiatric symptoms in elderly persons. Malabsorption accounts for the majority of cases. Vitamin B12 deficiency has been associated with neurologic, cognitive, psychotic, and mood symptoms, as well as treatment-resistance. Clinician awareness should be raised to accurately diagnose and treat early deficiencies to prevent irreversible structural brain damage, because current practice can be ineffective at identifying cases leading to neuropsychiatric sequelae. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
107
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(110 citation statements)
references
References 88 publications
2
107
0
1
Order By: Relevance
“…Some authors have found a strong causal relationship between cognitive decline and vitamin B 12 deficiency, while others have described the relationship as mere coincidence in the geriatric population. 3,5,12 The mechanism for cognition decline is the accumulation of methylmalonic acid secondary to nonactivation of methylmalonyl-CoA mutase, which is myelinotoxic. 35 We also observed a strong correlation of the neuropsychological scores with FA, ADC, and RD changes in some brain regions on DTI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have found a strong causal relationship between cognitive decline and vitamin B 12 deficiency, while others have described the relationship as mere coincidence in the geriatric population. 3,5,12 The mechanism for cognition decline is the accumulation of methylmalonic acid secondary to nonactivation of methylmalonyl-CoA mutase, which is myelinotoxic. 35 We also observed a strong correlation of the neuropsychological scores with FA, ADC, and RD changes in some brain regions on DTI.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Studies in elderly subjects suggest that vitamin B 12 deficiency is associated with cognitive decline and may contribute to Alzheimer dementia, 3,4 whereas others have failed to demonstrated an increased risk. 5,6 Subjects with B 12 deficiency may also show changes in the posterolateral column of the spinal cord on MR imaging. Clinical symptoms relating to neuropathy and spinal cord involvement, referred to as subacute combined degeneration (SACD) of the spinal cord, are common in adult subjects with B 12 deficiency.…”
mentioning
confidence: 99%
“…1 Symptoms are detailed in Table 2, 1,10,14 but the following may also be considered in relation to vitamin B 12 defi ciency.…”
mentioning
confidence: 99%
“…However, 2-year supplementation with vitamin B12 and folic acid in older adults with hyperhomocysteinemia showed that lowering Hcy concentrations does not reduce depressive symptoms, but it may have a small positive effect on health-related quality of life [49]. A study by Lachner et al suggested a supplementation dose of at least 1000 µg/ day might be more effective in reducing depressive symptoms [50]. Okereke et al reported that long-term, high-dose, daily supplementation with folic acid and vitamins B6 and B12 did not reduce overall depression risk in 4331 older women (mean age 63.6 years), without prior depression [51].…”
Section: Benefits Of Folic Acid Supplementationmentioning
confidence: 99%